WATER TRANSPORT AND GROWTH OF CASHEW (Anacardium occidentale L.) UNDER SOIL MECHANICAL IMPEDANCE - JOKO PITONO; TSUDA MAKOTO; YOSHIHIKO HIRAI (Jurnal Penelitian Tanaman Industri, 2015)
ABSTRACTThe ability to adapt to soil mechanical impedance was considered to support cashew growing in drought prone areas, since those areas are sometimes aggravated by problem on soil mechanical impedance. The response of water transport and growth under soil mechanical impedance was  evaluated  at  two  productive  cashew  accessions.  Two  cashew accessions, A3-1, that adapt well to drought stress, and a local accession Pangkep, and four levels of soil bulk densities of 0.75 g cm-3, 0.90 g cm-3, 1.00 g cm-3 and 1.24 g cm-3 under sufficient soil moisture conditions, were arranged   in   factorially completely   randomized   design   with   five replications. The response of shoot and root growth, transpiration and hydraulic  conductance  were  evaluated.  The  results  showed  that  the accession of A3-1 indicated a better to maintain root growth under soil mechanical impedance that produced thick root/total root length ratio and xylem area/transvesal root area ratio more than Pangkep. On the other hand, A3-1 was faster in reducing leaf area than Pangkep when subjected to increased level of soil bulk density treatments. Although the hydraulic conductance was not varied among the cashew accessions and had not a specific response trend to soil bulk density treatments, however, the increase of diurnal transpiration induced by increased level of soil bulk density treatment in A3-1 was higher than it in Pangkep. It is suggested that the ability to regulate the root and shoot growth and water transport under soil mechanical impedance condition was better in A3-1 than in Pangkep. Moreover, it might be a part attribute of drought tolerance on A3-1 accession.Keywords: cashew, soil mechanical impedance, growth, water transport ABSTRAKTransportasi Air dan Pertumbuhan Jambu Mente (Anacardium occidentale L.) pada Berbagai Hambatan Mekanik TanahKemampuan  adaptasi  terhadap  hambatan  mekanik  tanah  diper- kirakan  membantu  pengembangan  jambu  mente  di  wilayah  berlahan kering, mengingat kondisi wilayah tersebut sering diperparah oleh masalah hambatan mekanik tanah. Respon transportasi air tanaman dan pertum- buhan terhadap hambatan mekanik tanah dievaluasi pada dua aksesi jambu mente.  Dua  aksesi  jambu  mete,  A3-1  yang  adaptif  terhadap  stres kekeringan dan aksesi lokal, Pangkep, serta 4 level padatan tanah 0.75 g.cm-3, 0.90 g.cm-3, 1.00 g.cm-3, dan 1.24 g.cm-3  dengan kondisi lengas tanah dijaga selalu cukup, disusun dalam rancangan faktorial acak lengkap dengan lima ulangan. Respon pertumbuhan akar dan tajuk, transpirasi, dan daya hantar air tanaman dievaluasi. Hasil penelitian menunjukkan bahwa A3-1 lebih mampu menjaga pertumbuhan akar pada kondisi hambatan mekanik tanah dengan nilai rasio panjang akar tebal/panjang total akar dan rasio luas xylem/luas melintang akar lebih lebih besar daripada Pangkep. Pada sisi lain, A3-1 mengurangi luas daun lebih cepat dibanding Pangkep saat diberikan kenaikan perlakuan berat isi tanah. Meskipun tidak ada perbedaan daya hantar air tanaman di antara kedua aksesi dan tidak adanya pola respon spesifik terhadap perlakuan  padatan tanah, namun terjadi kenaikan transpirasi harian lebih besar pada A3-1 daripada Pangkep. Hasil ini mengindikasikan bahwa kemampuan A3-1 mengatur pertumbuhan dan transportasi  air  saat  mengalami  hambatan  mekanik  tanah  lebih  baik daripada Pangkep. Hal ini mungkin merupakan bagian dari sifat toleransi terhadap kekeringan pada aksesi A3-1.Kata kunci:  jambu mente, hambatan mekanik tanah, pertumbuhan, transportasi air